Laser therapy in wound healing associated with diabetes mellitus - Review - Raquel Gomes de Sousa; Keila de Nazaré Madureira Batista (Sociedade Brasileira de Dermatologia, 2016)
Abstract: The article discusses the results of a literature review on the application of low intensity laser therapy on the healing of wounds associated diabetes mellitus in the last 10 years. Objective: To determine the most effective parameter in healing wounds related to diabetes mellitus, as well as the most widely used type of laser. Methodology: consisted of bibliographic searching the databases Bireme, SciELO, PubMed/Medline and Lilacs by using the keywords related to the topic. Were selected from these keywords, papers discussing the use of laser on wounds associated with diabetes, published in the period 2005-2014, in Portuguese or English. Results: After analyzing the research, 12 studies consistent with the theme were selected. Conclusion: Based on this review, the studies that showed more satisfactory results in healing diabetic wounds were those who applied energy densities in the range of 3-5 J/cm2, power densities equal to or below 0.2 W/cm2 and continuous emission. The He-Ne laser with a wavelength of 632.8 nm was used more often.